Universal salvation - Harries, Richard (Theology, 2020)
The article looks at the moral considerations that indicate all shall be saved and the difficulties to this view presented by both a belief in free choice and the Scriptures. It considers two historical figures who point in the direction of universalism, Gregory of Nyssa and Julian of Norwich, and also some modern theologians such as Karl Barth and Austin Farrer who do not rule it out. It draws on the insights of poets and a novelist, and examines the concept of invincible grace, what it might mean and what it might imply.